1991
DOI: 10.1093/intimm/3.4.317
|View full text |Cite
|
Sign up to set email alerts
|

TNF inhibits malaria hepatic stages in vitro via synthesis of IL-6

Abstract: We examined the capacity of murlne recomblnant tumor necrosis factor (rmTNF) to induce an inhibitory effect at the hepatic stage on malaria induced by Plasmodium yoelii sporozoltes. When injected three times, 1.0 /ig of rmTNF was found to protect 78% of mice against a sporozolte challenge. In contrast, whatever the dose and the schedule of administration, no inhibition was observed when purified hepatocyte cultures were infected with P. yoelii. The addition of nonparenchymal hepatic cells to hepatocyte culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
3

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 18 publications
1
34
3
Order By: Relevance
“…The protection induced by spz/CQ immunization was found to be strictly dependent on NO, as inhibition of inducible NO synthase by treatment with a highly specific inhibitor, S-methyl-thiourea (21) completely reversed protection (Table VI). Previous work has shown that LS parasites are susceptible to radical nitrogen intermediates induced by different cytokines (IFN-␥, IL-6, or TNF-␣) or after immunization with irr.spz (32,(35)(36)(37). Thus, our results imply that in our immunization model, other cytokines may lead to NO-mediated killing.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The protection induced by spz/CQ immunization was found to be strictly dependent on NO, as inhibition of inducible NO synthase by treatment with a highly specific inhibitor, S-methyl-thiourea (21) completely reversed protection (Table VI). Previous work has shown that LS parasites are susceptible to radical nitrogen intermediates induced by different cytokines (IFN-␥, IL-6, or TNF-␣) or after immunization with irr.spz (32,(35)(36)(37). Thus, our results imply that in our immunization model, other cytokines may lead to NO-mediated killing.…”
Section: Discussionsupporting
confidence: 53%
“…The observation of some protection in the absence of IFN-␥R signaling suggests that an alternative pathway is operating (Table V). This pathway, however, does not seem to involve other cytokines such as IL-12, IL-6, or TNF-␣ (Table VI), which have been shown previously to inhibit LS development (32)(33)(34)(35)(36). The protection induced by spz/CQ immunization was found to be strictly dependent on NO, as inhibition of inducible NO synthase by treatment with a highly specific inhibitor, S-methyl-thiourea (21) completely reversed protection (Table VI).…”
Section: Discussionmentioning
confidence: 81%
“…We investigated whether poxvirus vaccination induced not only IFN-␥-producing, but also TNF-␣-producing CD8 ϩ T cells in the murine liver and whether they correlated with protection against sporozoite challenge. The induction of TNF-␣-producing T cells is of particular interest in malaria because TNF-␣ can inhibit both liver-and blood-stage parasites (23,24,29,36) and synergizes with IFN-␥ to induce nitric oxide and kill parasites (23,24).…”
Section: V␣14inkt Cells and Thus Vaccine Efficacy We Show That Intramentioning
confidence: 99%
“…Different mechanisms, involving both specific and non-specific components of the host response against infection, contribute to control malaria parasite development in the liver (Mazier et al, 1990;Rénia et al, 1991;Schofield et al, 1988;Schofield et al, 1989;Weiss et al, 1988;Weiss et al, 1990). Experimentally, there is evidence that acute phase proteins synthetized by the hepatocyte in response to cytokine stimulation also protect hepatocyte against sporozoite infection (Mellouk et al, 1987 1991a, 1991bPied et al, 1989Pied et al, , 1990. APPs are plasma proteins whose concentrations vary during an inflammatory reaction.…”
Section: Introductionmentioning
confidence: 99%
“…C-reactive protein, a major APP in humans, was found to inhibit the pre-erythrocytic stage of Plasmodium yoelii (Pied et al, 1989). Other APPs seem to be involved in inhibitory effects on parasite maturation (Nussler et al, 1991a). The extent to which acute phase reactants participate in resistance to plasmodial infection in humans exposed to natural infection has been studied.…”
Section: Introductionmentioning
confidence: 99%